Dynamic Lower Extremity Deformity in Children With Pseudoachondroplasia. Issue 3 (March 2018) - Gaebe, Glen; Kruse, Richard; Rogers, Kenneth; Mackenzie, William G.; Holmes, Laurens
Abstract : Background: Pseudoachondroplasia is a diverse group of skeletal dysplasias with a common pathway of altered cartilage oligomeric matrix protein (COMP) production. This rhizomelic dwarfism is commonly associated with deformities of the lower extremities, accelerated osteoarthritis, and ligamentous laxity. One of the most common alignment problems is coronal knee angulation which combined with tibial torsion, results in a complex deformity. The outcome of surgical correction of these deformities is variable. Methods: This study used 3-dimensional gait analysis to describe the kinematic deformities in 12 children (aged 3 to 15 y) and compared them to the static deformities measured on standing anteroposterior radiograph. Results: Both gait analysis and radiographs showed large variability in the coronal deformities but strong correlation to each other. Gait analysis showed mean varus alignment of the knee to be 13.5±13.1 degrees; that mean is not statistically different from radiographs, which showed a mean varus of 16.2±17.1 degrees. The correlation coefficient between radiographic and kinematic measurement was 0.70. The kinematic internal tibial torsion measured an average 15±19 degrees, which was moderately correlated to knee varus ( r =0.45, P <0.01). Conclusions: Measurements of varus-valgus alignment correlated well between gait analysis and radiographs. Tibial torsion correlated with varus. In the absence of gait analysis, anteroposterior standing leg length radiographs with the patella facing foreward can be used to assess deformity. As this study does not correlate these measurements to postoperative results, an appropriately powered prospective study and further investigation of biological effects of altered cartilage oligomeric matrix protein production are needed to explain the variable surgical outcomes. Level of Evidence: Level IV—case series without control group).